2009
DOI: 10.3324/haematol.2009.018028
|View full text |Cite
|
Sign up to set email alerts
|

HAMP promoter mutation nc.-153C>T in non p.C282Y homozygous patients with iron overload

Abstract: ) and the Basque population: contribution of HLA class I molecular markers to their evolutionary history. HAMP promoter mutation nc.-153C>T in non p.C282Y homozygous patients with iron overloadIn a recent paper, Island and colleagues 1 described a heterozygous hepcidin (HAMP) promoter mutation, nc.-153C>T, which in association with HFE p.C282Y homozygosity appeared to lead to very severe iron overload (IO). They demonstrated in vitro that this HAMP mutation decreases transcriptional activity of the hepcidin pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
5
1
Order By: Relevance
“…The prevalence of this mutation in the general population seems to be low. It was found at an allele frequency of 0.0045 in our region in southern France (27) and was reported at an allele frequency of 0.0049 in healthy individuals from Galicia (Spain) (39). On the other hand, it was neither found in 200 normal chromosomes from Brittany, nor in 785 HEIRS study participants.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…The prevalence of this mutation in the general population seems to be low. It was found at an allele frequency of 0.0045 in our region in southern France (27) and was reported at an allele frequency of 0.0049 in healthy individuals from Galicia (Spain) (39). On the other hand, it was neither found in 200 normal chromosomes from Brittany, nor in 785 HEIRS study participants.…”
Section: Discussioncontrasting
confidence: 55%
“…This mutation has been linked to severe IO . We previously showed that the allele frequency of this variant was 0.004 in the population of our area , whereas it was 0.09 among the 13 iron‐overloaded HCC patients of this series ( P = 0.0013). This mutation was also found in one additional patient in the control group of subjects with abnormal iron parameters (allele frequency: 0.028; P = 0.15 when compared to the general population of the area).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Genetic modifiers increasing iron stores, such as the presence of the HFE C282Y mutation or a HAMP mutation and possibly gender (male patient 3), were accompanied by high LIC and increased hemolysis . Indeed, heterozygosity for the HFE C282Y mutation (patient 1) and the HAMP :c.‐153C>T mutation (patients 3 & 4) is known contributing factor to IO in association with other genetic or acquired conditions . Patient 3 had a more severe iron overload than patient 2 (his mother) who did not carry the HAMP mutation and than patient 4 (his sister) who did carry the same HAMP mutation but had initially concomitant iron deficiency due to increased gynecological bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…153C>T mutation (patients3 & 4) is known contributing factor to IO in association with other genetic or acquired conditions 5. Patient 3 had a more severe iron overload than patient 2 (his mother) who did not carry the HAMP mutation and than patient 4 (his sister) who did carry the same HAMP mutation but had initially concomitant iron deficiency due to increased gynecological bleeding.…”
mentioning
confidence: 99%